New and little known species of ptyctimous mites (Acari, Oribatida) from Madagascar - Niedbała, Wojciech; Starý, Josef (Zootaxa, 2016)
In six sifting litter samples from Madagascar, altogether 26 species of ptyctimous mites, belonging to four families and 11 genera, were found. Three new species, Arphthicarus phoxos sp. nov., Notophthiracarus parapaulianus sp. nov. and Atropacarus (Hoplophorella) paralemurius sp. nov. are described and figured. Keys for species of genera and subgenera Arphthicarus, Notophthiracarus and Atropacarus (Hoplophorella) from Madagascar are presented.